Unbalanced translocations arise from diverse mutational mechanisms including chromothripsis - Weckselblatt, Brooke; Hermetz, Karen E.; Rudd, M. Katharine (Genome Research, 2015)
Unbalanced translocations are a relatively common type of copy number variation and a major contributor to neurodevelopmental disorders. We analyzed the breakpoints of 57 unique unbalanced translocations to investigate the mechanisms of how they form. Fifty-one are simple unbalanced translocations between two different chromosome ends, and six rearrangements have more than three breakpoints involving two to five chromosomes. Sequencing 37 breakpoint junctions revealed that simple translocations have between 0 and 4 base pairs (bp) of microhomology (n = 26), short inserted sequences (n = 8), or paralogous repeats (n = 3) at the junctions, indicating that translocations do not arise primarily from nonallelic homologous recombination but instead form most often via nonhomologous end joining or microhomology-mediated break-induced replication. Three simple translocations fuse genes that are predicted to produce in-frame transcripts of SIRPG-WWOX, SMOC2-PROX1, and PIEZO2-MTA1, which may lead to gain of function. Three complex translocations have inversions, insertions, and multiple breakpoint junctions between only two chromosomes. Whole-genome sequencing and fluorescence in situ hybridization analysis of two de novo translocations revealed at least 18 and 33 breakpoints involving five different chromosomes. Breakpoint sequencing of one maternally inherited translocation involving four chromosomes uncovered multiple breakpoints with inversions and insertions. All of these breakpoint junctions had 0–4 bp of microhomology consistent with chromothripsis, and both de novo events occurred on paternal alleles. Together with other studies, these data suggest that germline chromothripsis arises in the paternal genome and may be transmitted maternally. Breakpoint sequencing of our large collection of chromosome rearrangements provides a comprehensive analysis of the molecular mechanisms behind translocation formation.
10.1101/gr.191247.115